Regional geology, setting and sedimentology of Sibudu Cave - Pickering, R. (Southern African Humanities, 2021)
Sibudu Cave has rich, well preserved Middle Stone Age deposits with a centimetre-scale stratigraphy. The fine-grained, ashy sediments lack sedimentary structures and contain abundant cultural material (stone tools in particular); this implies that the deposits are of anthropogenic origin. The space available for occupation, and for accumulation of deposit, is controlled by the morphology of the floor. This is seen in the similarity between the dip angles of the wall and the layers of the deposit. The archaeological deposits are concentrated in the sheltered northern part of the shelter, where the most suitable space is available. To cite this article: Pickering, R. 2006. Regional geology, setting and sedimentology of Sibudu Cave. Southern African Humanities 18 (1): 123-29.